The Discrete-Analytical Solution Method for Investigation Dynamics of the Sphere with Inhomogeneous Initial Stresses - Akbarov, Surkay D.; Guliyev, Hatam H.; Sevdimaliyev, Yusif M.; Yahnioglu, Nazmiye (TECH SCIENCE PRESS, 2018)
The paper deals with a development of the discrete-analytical method for the solution of the dynamical problems of a hollow sphere with inhomogeneous initial stresses. The examinations are made with respect to the problem on the natural vibration of the hollow sphere the initial stresses in which is caused by internal and external uniformly distributed pressure. The initial stresses in the sphere are determined within the scope of the exact equations of elastostatics. It is assumed that after appearing this static initial stresses the sphere gets a dynamical excitation and mechanical behavior of the sphere caused by this excitation is described with the so-called three-dimensional linearized equations of elastic wave propagation in initially stressed bodies. For the solution of these equations, which have variable coefficients, the discrete analytical solution method is developed and applied. In particular, it is established that the convergence of the numerical results with respect to the number of discretization is very acceptable and applicable for the considered type dynamical problems. Numerical results on the influence of the initial stresses on the values of the natural frequencies of the hollow sphere are also presented and these results are discussed.
Keywords: Discrete-analytical solution method; initial stress; hollow sphere; natural frequency; dynamical problem; COMPRESSIBLE VISCOUS-FLUID; SHELL-THEORY ANALYSIS; MOVING ELASTIC PLATE; VIBRATION ANALYSIS; NATURAL VIBRATION; MIDDLE LAYER; WAVES; Computer Science; Materials Science